The Effects of Filter Type and Warm-Up Time on Pellet Durability Index Using the Holmen NHP100 Portable Pellet Tester - C. E. Evans; R. N. Kort; M. Saensukjaroenphon; H. K. Wecker; C. B. Paulk; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2019)
The Holmen NHP100 (TekPro Ltd, Norfolk, UK) is a portable forced air pellet tester commonly used by the feed industry to determine the pellet durability index (PDI). The objective of this study was to determine the effect of filter type and machine warm-up time on PDI. A corn-soybean meal-based grower diet was conditioned at 185°F for 30 sec and subsequently pelleted using a laboratory pellet mill (Model CL5 California Pellet Mill Co., Crawfordsville, IN) equipped with a 0.16- × 0.5-in die. Production rate was 120 lb/h. Once cool, pellets were analyzed for PDI using the NHP100 with a 60-sec run time. Air temperature and pressure within the NHP100 were recorded throughout the experiment. Treatments were arranged in a 3 × 8 factorial with varying filters (none, factory tissue filter, or commercial paper towel filter) and machine warm-up time (0, 3, 6, 9, 12, 15, 18, or 21 min). There were three replicates per treatment. Pellets were sifted before and after analysis for separation of fines and pellets using a U.S. #6 standard sieve. There was a filter × warm-up time interaction (P ≤0.05) for air temperature. The air temperature without warm-up time (0 min) was greater with the factory filter and paper towel compared to no filter. Air temperature remained similar regardless of filter type as the warm-up time increased from 6 to 21 min There was a filter × warm-up time interaction (P ≤0.05) for air pressure. At 0 min warm-up time, there were no differences in air pressure between none, factory and paper towel filters. At 3 to 21 min warm-up time, air pressure remained similar between factory and paper towel filters, while no filter was greater than the paper towel filter. There was a filter × warm-up time interaction (P ≤0.05) for PDI. For no filter, increasing warm-up time from 0 to 6 min increased PDI with no further increase from 6 to 21 min. However, there were no differences in PDI with increasing warm-up time when using the factory filter or paper towel. Using the factory filter or paper towel had similar PDI, but resulted in greater PDI compared to no filter. In conclusion, warm-up time did not influence air temperature, pressure, or PDI when using a filter. Therefore, it is suggested to use a filter when conducting PDI analysis using the Holmen NHP 100.
Keywords: pelleting; pellet durability index; Holmen NHP100